Implications of the capital structure on the efficiency of stock pricing : Analytical research (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to know the effect of capital structure on the efficiency of stock pricing. The research was applied in companies listed in the Iraqi market and for a period (2017-2020). That affects the value of the shares of the companies listed in it and the risks associated with it, as the risks are a dynamic process that changes over time depending on the variables that affect the general development of the economy, so these fluctuations should be taken into account to achieve maximizing returns and reducing risks and what is reflected in stock prices in the Iraqi markets Securities, through which the following question was asked: How does investment risk affect the efficiency of stock pricing in the Iraq Stock Exchange? In light of this, the importance of the research and its objectives were determined, and the research methodology relies on the analytical method as it is more appropriate to the nature and scope of the research, in order to reach the results that the research aims at.